Responding to COVID-19 supply chain risks: Insights from supply chain change management, total cost of ownership and supplier segmentation theory - Remko I. van Hoek (Logistics, 2020)
The COVID-19 pandemic is causing risks and disruptions in most supply chains. As supply chain managers are responding to these risks, several theories may inform those efforts. In this paper, we explore across seven companies in different industries, supply chain positions and countries, how lessons from total costs of ownership, supplier segmentation and supply chain change management theory may apply to efforts to respond to COVID-19 supply chain risks and disruptions. The findings indicate that the pandemic forces companies to consider total costs more holistically, beyond the purchase price, and that collaboration with suppliers and developing new sources of supply is of growing importance to reduce risk in the supply chain. However, the change involved in responding to risks will take time, and for many companies, the hardest work is still ahead. Our findings also paint a more nuanced and complex picture than offered in the popular press; the focus on nearshoring does not necessarily mean leaving China and the switch in total costs of ownership may only be partial and temporal. Limitations of the theories considered are identified and resulting suggestions for managers and further research are developed.
Keywords: 650; change management; COVID-19 response; supplier segmentation; total cost of ownership